2019
DOI: 10.3390/catal9100799
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Friendly Nanoporous Titanium Dioxide with Enhanced Photocatalytic Activity

Abstract: Nanoporous TiO2 anatase was environment-friendly prepared using coffee husk extract (CHE) as bio-template instead of hazardous chemicals and solvents and ultrasonic waves. Caffeine and caffeic acid were found to be the main compounds in CHE to modify the morphology of TiO2. The properties of as-prepared titanium dioxide particles were determined by different characterization techniques. The results demonstrate the formation of a meso/macro-porous channel consisting of small TiO2 particles (8–10 nm). The as pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 41 publications
(55 reference statements)
1
9
0
1
Order By: Relevance
“…The higher number of sharp peaks and broad bands in the TiO 2 NPs_CE spectra could be attributed to the presence of free caffeine in addition to those that refer to flavonoids as in TiO 2 NPs_PPE. The recorded vibrations of caffeine in this study are in accordance with previous reports [32,40]. These bioactive molecules function as templates during the synthesis process to maintain phase stability and prevent the overgrowth and aggregation of TiO 2 NPs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The higher number of sharp peaks and broad bands in the TiO 2 NPs_CE spectra could be attributed to the presence of free caffeine in addition to those that refer to flavonoids as in TiO 2 NPs_PPE. The recorded vibrations of caffeine in this study are in accordance with previous reports [32,40]. These bioactive molecules function as templates during the synthesis process to maintain phase stability and prevent the overgrowth and aggregation of TiO 2 NPs.…”
Section: Discussionsupporting
confidence: 91%
“…Based on our current findings, which revealed that the green-synthesized TiO 2 NPs using CE displayed smaller sizes and a greater zeta potential negativity than those synthesized from PPE, the formation of higher clusters could be observed in TiO 2 NPs_PPE (439.6 nm by DLS, 85.6 nm by TEM) on the surface of the seeds, whereas the TiO 2 NPs_CE (45.14 nm by DSL, 79.6 nm by TEM) showed individual nanoparticles and some clusters. In the same context, Al Qarni et al [32] succeeded in synthesizing nanoporous anatase-phase TiO 2 using coffee husk extract with a small-scale size of 7.5 nm, whereas Abu-Dalo et al [31] synthesized TiO 2 NPs using PPE with a Z-average size of 620 nm and zeta potential of 6.95 mV. XRD data also confirmed that crystalline TiO 2 NPs exhibited a strong anatase phase with 2θ values of 25.28 • and 48.37 • , and the small size was proven by broad peaks [33], which concur with the JCPDS file No.…”
Section: Discussionmentioning
confidence: 94%
“…In the literature, a plethora of synthetic routes has been proposed for the preparation of nanosized TiO 2 with photocatalytic antimicrobial properties; here we focus our attention on sol-gel and hydrothermal methods (Figure 1), as they have been regarded, so far, among the promising techniques for the large scale production of TiO 2 NPs, owing to their user-and environment-friendly and cost effective procedures [6][7][8][9]. However, for the sake of brevity, herein we report only a small selection of the numerous examples reported in literature and we direct the readers to more specific papers [8,10,11].…”
Section: Synthesis Of Photocatalytic Tio 2 Nanoparticles With Antimic...mentioning
confidence: 99%
“…Three rounds of dye degradation were completed with same batch of the photocatalyst by taking fresh dye solution each time. [29] Since tested TiO 2 catalyst consisted of mixed anatase and rutile phases, the rutile phase contributes to the thermodynamical stability of the catalyst. It is desired that degradation efficiency should not decrease on recycling.…”
Section: Recyclability Of the Photocatalystmentioning
confidence: 99%